Japanese Management between Tradition and Reform - Camelia-Cristina Dragomir (Amfiteatru Economic)
Today, the world is facing multiple challenges with concerning economic implications and disturbing social consequences. The successful national experiences, those which drew the attention in the course of time by the amazing economic results they achieved, can be an analyses and instructive source. The interest that specialists give to these experiences proves the importance which the knowledge of those economic and management models that proved their success in time has for the future of mankind. An example in this sense is the Japanese management model, one of the most discussed subjects in the scientific community and not only. The amazing evolution of Japan, the advanced stage of development of the Nipponese corporations and of the management system open a wide range of analysis. This challenging phenomenon for the world economy continues to arise interest, still being a current and necessary theme of study.